2019
DOI: 10.1109/tvcg.2018.2854737
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Label Design on Search Performance and Noticeability in Wide Field of View Augmented Reality Displays

Abstract: In Augmented Reality (AR), search performance for outdoor tasks is an important metric for evaluating the success of a large number of AR applications. Users must be able to find content quickly, labels and indicators must not be invasive but still clearly noticeable, and the user interface should maximize search performance in a variety of conditions. To address these issues, we have set up a series of experiments to test the influence of virtual characteristics such as color, size, and leader lines on the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…It has further been shown that typical eye movements mostly feature a predominance of horizontal saccades (leftwards or rightwards) compared to other directions (vertical or oblique angle saccades) when viewing scenes [29]. Regarding search behaviour in AR, there also seems to be a tendency for horizontal search patterns [14], which causes targets to enter the FOV more often through horizontal head movements [56].…”
Section: User Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has further been shown that typical eye movements mostly feature a predominance of horizontal saccades (leftwards or rightwards) compared to other directions (vertical or oblique angle saccades) when viewing scenes [29]. Regarding search behaviour in AR, there also seems to be a tendency for horizontal search patterns [14], which causes targets to enter the FOV more often through horizontal head movements [56].…”
Section: User Studiesmentioning
confidence: 99%
“…In terms of visual transition, we extended the existing EdgeRadar method by a transition cue as soon as the augmented information enters the FOV. We introduced a short blinking color change from blue to red as this visual change has been shown to work well in the periphery and potentially being able to incite drawing attention in relation to FOV [56]. Furthermore, the red color was chosen in particular because it provides a good color contrast to the proximity cue and was shown to have an impact on attention behaviour [58].…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings showed that whilst spatial placement of labels affected legibility, the improved spatial correlation compensated for this, showing the impact of spatial cues on overall understanding. More recently, in examining the use of labels in the user's periphery, Kruijff et al [17] found limited FOV of the label display severely limits search performance. This can be addressed by appropriate label rendering methods, however, rendering must still take place within the limited FOV of the display.…”
Section: General Positioning Depth and Sizing Cuesmentioning
confidence: 99%
“…This work focuses on improving multiscale navigation in the context of horizontally situated interactive maps, viewed using wearable AR (Figure 1). With the aim of extending these developments in future to collaborative interaction with 3D maps, we begin this exploration with single-user interaction with 2D maps, using a wide-FoV, video see-through AR platform [38,57]. While in-air gestures have been explored for large wall displays [53,65,69] and mobile devices [28,36], these previous developments use large arm motions or small finger movements that do not necessarily transfer directly to wearable AR and horizontal maps.…”
Section: Introductionmentioning
confidence: 99%